2022
DOI: 10.3389/fnut.2022.965073
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on extraction, purification, structure and biological activity of Dendrobium officinale polysaccharides

Abstract: Dendrobium officinale Kimura et Migo (D. officinale) is a traditional medicinal and food homologous plant that has been used for thousands of years in folk medicine and nutritious food. Recent studies have shown that polysaccharide is one of the main biologically active components in D. officinale. D. officinale polysaccharides possess several biological activities, such as anti-oxidant, heptatoprotective, immunomodulatory, gastrointestinal protection, hypoglycemic, and anti-tumor activities. In the past decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…The monosaccharide composition is the most fundamental and core research object in plant polysaccharide research. It is closely related to the physicochemical properties, structural characteristics, and structure–activity relationship of polysaccharides [ 19 ]. In this study, the dry and fleshy stems of Cynomorium songaricum were used to isolate and purify CSP-III, whose molecular weight was determined to be 4,018,234 Da and the monosaccharide composition included Man, GlcA, GalA, Rha, Glc, Gal, and Ara at a molar ratio of 0.01:0.11:0.03:0.57:0.02:0.32:1.…”
Section: Discussionmentioning
confidence: 99%
“…The monosaccharide composition is the most fundamental and core research object in plant polysaccharide research. It is closely related to the physicochemical properties, structural characteristics, and structure–activity relationship of polysaccharides [ 19 ]. In this study, the dry and fleshy stems of Cynomorium songaricum were used to isolate and purify CSP-III, whose molecular weight was determined to be 4,018,234 Da and the monosaccharide composition included Man, GlcA, GalA, Rha, Glc, Gal, and Ara at a molar ratio of 0.01:0.11:0.03:0.57:0.02:0.32:1.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrobium officinale Kimura et Migo ( D. officinale ) is an orchid plant with both medicinal and edible uses. D. officinale contains many bioactive components, including polysaccharides, polyphenols, flavonoids, and alkaloids, among which polysaccharides (DOPs) are the main one [ 24 , 25 , 26 ]. Zeng et al [ 27 ] reported that DOPs reduced H 2 O 2 -induced apoptosis in human gastric mucosal epithelial cells by decreasing ROS levels and improving cell nuclear morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, dendrobium polysaccharides have been prepared via hot water extraction, but it is an energy-intensive and time-consuming procedure. Therefore, ultrasonic, microwaves, acids, bases, and enzymes are used to assist extraction to improve extraction efficiency [ 26 ]. Enzyme-assisted extraction (EAE) is a gentler method than other extraction methods and is effective in breaking down cell walls and proteins to facilitate the release of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Tea is a drink made from the leaves or buds of the tea plant, which originated in China and has the longest history. There are numerous active ingredients in tea: tea polyphenols, tea polysaccharides, amino acids, alkaloids, vitamins, and so on [1]. Theophylline is not only one of the main flavor components in tea, but also has beneficial pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%